Development of an Icariin-Loaded Bilosome-Melittin Formulation with Improved Anticancer Activity against Cancerous Pancreatic Cells - Nabil A. Alhakamy; Shaimaa M. Badr-Eldin; Waleed S. Alharbi; Mohamed A. Alfaleh; Omar D. Al-hejaili; Hibah M. Aldawsari; Basma G. Eid; Rana Bakhaidar; Filippo Drago; Filippo Caraci; Giuseppe Caruso (MDPI AG, 2021)
Pancreatic cancer currently represents a severe issue for the entire world. Therefore, much effort has been made to develop an effective treatment against it. Emerging evidence has shown that icariin, a flavonoid glycoside, is an effective anti-pancreatic cancer drug. Melittin, as a natural active biomolecule, has also shown to possess anticancer activities. In the present study, with the aim to increase its effectiveness against cancerous cells, icariin-loaded bilosome-melittin (ICA-BM) was developed. For the selection of an optimized ICA-BM, an experimental design was implemented, which provided an optimized formulation with a particle size equal to 158.4 nm. After estimation of the release pattern, the anti-pancreatic cancer efficacy of this new formulation was evaluated. The MTT assay was employed for the determination of half maximal inhibitory concentration (IC50), providing smaller IC50 for ICA-BM (2.79 ± 0.2 µM) compared to blank-BM and ICA-Raw (free drug) against PNAC1, a human pancreatic cancer cell line isolated from a pancreatic carcinoma of ductal cell origin. Additionally, cell cycle analysis for ICA-BM demonstrated cell arrest at the S-phase and pre-G1 phase, which indicated a pro-apoptotic behavior of the new developed formulation. The pro-apoptotic and anti-proliferative activity of the optimized ICA-BM against PNAC1 cells was also demonstrated through annexin V staining as well as estimation of caspase-3 and p53 protein levels. It can be concluded that the optimized ICA-BM formulation significantly improved the efficacy of icariin against cancerous pancreatic cells.